Preparation method of composite positive electrode material

By adding specific precursors and dopants to the preparation process of sodium battery positive electrode materials, the problem of insufficient performance of existing materials is solved, and higher cyclic stability and electrochemical performance are achieved.

CN119627084APending Publication Date: 2025-03-14ZHEJIANG SHANGAO NEW ENERGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411908389.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The cycle stability and rate performance of existing sodium battery positive electrode materials still need to be improved, limiting the cost and energy density of sodium ion batteries.

Method used

By using the preparation method of composite positive electrode material, a composite positive electrode material with improved performance is obtained by adding Na0.67Ni0.33-xMn0.67VxO2 precursor and Na3V2O2 (PO4)2F during the coating process, and after thorough mixing, drying and calcining, etc.

Benefits of technology

It significantly improves grinding efficiency and product performance, improves the flowability, dispersion and stability of the cathode material, and improves the electrochemical and cyclic stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a composite positive electrode material. The preparation method comprises the following steps: uniformly distributing a Na < 0.67 > Ni < 0.23 > Mn < 0.67 > V < 0.1 > O < 2 > precursor in an anhydrous alcohol solution; adding Na3V2O2 (PO4) 2F, mixing, drying and calcining to obtain a composite positive electrode material; the grinding aid disclosed by the invention is obtained by reacting vanadium dimercaptosuccinate, sodium oleate, styrylboronic acid diethanolamine ester, methylbenzene and sodium ethoxide. After the V element is doped into the positive electrode material, the average particle size of the layered oxide is reduced; the reduction is beneficial to furthest reducing the diffusion distance of Na < + > and enhancing the contact between the active material and the electrolyte, so that the rate capability of the material is improved; according to the prepared composite positive electrode material, the phase structure of the positive electrode material is maintained, meanwhile, the stability of the material in ambient air is effectively improved, the side reaction between an electrode plate and an electrolyte is relieved, and the ion diffusion capacity is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium battery positive electrode materials, in particular to a method for preparing a composite positive electrode material. Background Art

[0002] Currently, lithium-ion batteries (Li-ion batteries) are the leading energy storage technology due to their long life and high energy density. The total amount of lithium resources in the world is estimated to be between 15 million and 30 million tons, but these resources are unevenly distributed geographically. At the same time, the recovery rate of lithium from waste Li-ion batteries is extremely low, less than 1%, which is almost negligible. Faced with the potential shortage of lithium resources, researchers are looking for more cost-effective and easier to obtain alternative materials. In recent years, sodium-ion batteries (Na-ion batteries) have once again attracted widespread attention from the scientific research community due to their huge sodium reserves on Earth, low cost, and growing demand for large-scale renewable electrochemical energy storage systems. Na-ion batteries present several potential advantages, including: (1) abundant and widely distributed sodium resources, resulting in relatively low cost; (2) sodium ions are compatible with currently used lithium battery production equipment; (3) aluminum foil, which is cheaper than copper foil, can be used as the positive and negative current collectors in sodium batteries. In addition, since there is no over-discharge problem, the overall cost of the battery can be further reduced; in summary, compared with lithium battery technology, Na-ion batteries have significant advantages in terms of sustainable development and economic benefits. These characteristics indicate that sodium-ion batteries have a favorable competitive position in the future market. The development of sodium-ion batteries urgently requires electrode materials with high capacity and stability. In sodium-ion battery systems, cathode materials are the core factor limiting their cost and energy density. Researching and developing high-performance cathode materials has become particularly critical.

[0003] Chinese patent CN115133002B: provides a sodium battery positive electrode material, the chemical formula of the sodium battery positive electrode material is as follows: xNaMBO3.yNa2Ti3O7.zNa3V2(BO3)3 / C; wherein the molar ratio of x, y and z is 0.94-0.96:0.02-0.03:0.02-0.03; M is Fe and Mn, and the molar ratio of Fe to Mn is 8-9:1-2; the mass fraction of carbon in the sodium battery positive electrode material is 1.2-1.5%.

[0004] Chinese patent CN116435481A: relates to a method for preparing a sodium battery positive electrode material with a high configuration entropy surface by a solid phase method, comprising the following steps: (1) setting a chemical formula A of the surface material, wherein the chemical formula A must contain at least two elements that are beneficial to the formation of a sodium-containing layered oxide material, and at least three doping elements; (2) weighing compounds of corresponding metal elements according to the chemical formula A, mixing them evenly to obtain an A-precursor; (3) obtaining a layered positive electrode material B, mixing it evenly with the A-precursor to obtain B (A-precursor); heat treating the B (A-precursor) to obtain a sodium battery positive electrode material with a high configuration entropy surface.

[0005] Chinese patent CN117069162B: Provides a doped and coated sodium battery positive electrode material, its preparation method and use, including: preparing a positive electrode material precursor, mixing it with a sodium source and sintering it to obtain a positive electrode material; adding nanocellulose and conductive nanoparticles to a Tris buffer solution to obtain a dispersion; adding dopamine to the dispersion and mixing and reacting it, purifying and drying it to obtain a coating material; adding the positive electrode material to a dispersion solvent to form a suspension, adding the coating material, mixing it evenly, filtering, washing and drying it to obtain a coated intermediate product, and sintering it to obtain a sodium battery positive electrode material.

[0006] The cycle stability and rate performance of the positive electrode materials prepared by the above patents and prior arts still need to be improved. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a method for preparing a composite positive electrode material, and the operating steps are as follows: S1: During the coating process, 80-100 parts of Na 0.67 Ni 0.33-x Mn 0.67 V x The O2 precursor is evenly distributed in 200-300 parts of anhydrous alcohol solution; then 3-7 parts of Na3V2O2(PO4)2F are added, and after 8-12 hours of thorough mixing and strong stirring, the mixture is dried at 50-60°C for 8-12 hours to obtain a solid powder; S2: calcining the solid powder at 500-650° C. for 3-5 h in an air atmosphere to obtain a composite positive electrode material.

[0008] The Na 0.67 Ni 0.33-x Mn 0.67 V x The preparation method of O2 precursor is as follows: A1: 60-70 parts of sodium source, 15-20 parts of nickel source, 70-80 parts of manganese source, 15-20 parts of vanadium pentoxide, and 0.08-0.4 parts of grinding aid are mixed uniformly; A2: Add the mixture into a ball mill at 300-400 r / min, add 50-70 parts of anhydrous ethanol, ball mill for 90-120 minutes, and dry; A3: The ball-milled powder is pressed into a sheet, placed in a muffle furnace, calcined at 700-950°C for 8-12 hours in an air atmosphere, and then cooled to room temperature to obtain Na 0.67 Ni 0.33-x Mn 0.67 V x O2 precursor.

[0009] The preparation method of Na3V2O2(PO4)2F is as follows: B1: Add 15-20 parts of V2O5 and 30-40 parts of oxalic acid to 60-70 parts of deionized water and stir at 60-70°C for 40-60 minutes; B2: Add 10-15 parts of NaF and 8-12 parts of NH2H2PO4 to 10-20 parts of deionized water, stir to dissolve, and then add to the solution of B1; B3: The solution obtained in B2 is placed in a polytetrafluoroethylene autoclave, and subjected to hydrothermal treatment at 150-170°C for 8-12 hours in a forced air drying oven, and then cooled to room temperature; the obtained blue substance is washed with deionized water three times, and finally dried at 60-70°C for 8-12 hours; B4: Then, under N2 atmosphere, the powder obtained in B3 was sintered at 500-650°C at a rate of 3°C per minute for 90-120 min to obtain Na3V2O2(PO4)2F.

[0010] The sodium source is one of sodium carbonate, sodium hydroxide, sodium bicarbonate and sodium chloride.

[0011] The nickel source is one of nickel oxide and nickel hydroxide.

[0012] The manganese source is one of manganese sulfate, manganese oxide and manganese carbonate.

[0013] The preparation method of the grinding aid is: The stirred kettle is kept under nitrogen condition and nitrogen is flushed for 10-30 minutes. 10-20 parts of vanadium dimercaptosuccinate, 30-50 parts of sodium oleate, 2-5 parts of styryl boric acid diethanolamine ester (CAS No. 411222-52-1), 200-300 parts of toluene and 3-7 parts of sodium ethoxide are stirred and reacted at 80-90° C. for 100-150 minutes. After the reaction is completed, toluene is removed by reduced pressure distillation to obtain a grinding aid.

[0014] The preparation method of vanadium dimercaptosuccinate is as follows: According to weight, 20-40 parts of dimercaptosuccinic acid, 18-36 parts of vanadium nitrate and 500-700 parts of water are stirred for reaction at 40-50° C. for 100-150 minutes, and water is distilled off to obtain vanadium dimercaptosuccinate.

[0015] Reaction mechanism Basic principles of thiol addition reaction: thiol (-SH) is a strong nucleophile that can undergo addition reaction with carbon-carbon double bonds (C=C); this reaction usually proceeds through the Michael addition mechanism, in which the thiol attacks the electron-deficient carbon atom on the double bond to form a new carbon-sulfur bond (CS); in vanadium dimercaptosuccinate, each thiol can participate in such reaction independently.

[0016] The first reaction of thiol with sodium oleate: The carbon-carbon double bond in sodium oleate (CH3(CH2)7COONa) can undergo addition reaction with thiol.

[0017] The second thiol reacts with styryl boric acid diethanolamine ester: styryl boric acid diethanolamine ester contains a styrene group, and the thiol attacks the double bond of the styrene group to form a new carbon-sulfur bond, and at the same time the double bond opens to form a single bond structure; this reaction follows the typical Michael addition mechanism.

[0018] Technical Effects The present invention provides a method for preparing a composite positive electrode material. Compared with the prior art, the present invention has the following significant effects: 1. Improve grinding efficiency: The addition of grinding aids can significantly reduce the direct friction between grinding media and reduce energy loss, thereby improving grinding efficiency under the same conditions; this means that the same grinding effect can be achieved in a shorter time, or better product quality can be obtained in the same time.

[0019] 2. Improve product performance: Due to the special structure and composition of the grinding aid, the grinding aid contains the following structural features: one end is connected to sodium oleate; the other end is connected to styryl boric acid diethanolamine ester through a newly formed carbon-sulfur bond; this structure makes the grinding aid amphiphilic at the molecular level, that is, it has both hydrophilic and hydrophobic parts, which is beneficial to its dispersion and action in the grinding medium; because it contains elements such as vanadium and fluorine, these elements may promote the grinding process in some way, improve grinding efficiency and product quality; it can effectively coat and modify the product particles during the grinding process, thereby improving the product's fluidity, dispersibility and stability and other properties. DETAILED DESCRIPTION

[0020] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description in combination with embodiments and comparative examples: Battery assembly: The positive electrode materials prepared in the embodiment and the comparative example were respectively used as active materials, and the active material: ultrafine carbon powder (SP): polyvinylidene fluoride were mixed in a mass ratio of 90:5:5, and N-methylpyrrolidone (NMP) was added to make a viscous glue, which was coated on aluminum foil and baked in a vacuum drying oven at 120°C for 12 hours to obtain a positive electrode plate; a metal sodium plate was used as a negative electrode; glass fiber (Waterman) was used as a diaphragm, and 1mol / LNaPF6 (EC and PC with a solvent mass ratio of 1:1) was used as an electrolyte to assemble a 2032 button-type sodium ion battery in an Ar protective glove box. Using a LANDCT2001A tester, the battery was charged to 3.0V at a rate of 0.5C, and then discharged to 0.01V at a rate of 0.5C, and a cyclic charge and discharge test was performed to test the initial charge and discharge efficiency and the capacity retention rate after 200 cycles of charge and discharge.

[0021] Example 1 A method for preparing a composite positive electrode material, the operating steps of which are: S1: During the coating process, 80gNa 0.67 Ni 0.23 Mn 0.67 V 0.1 The O2 precursor was evenly distributed in 200 g of anhydrous alcohol solution; then 3 g of Na3V2O2(PO4)2F was added, and after 8 h of thorough mixing and strong stirring, it was dried at 50°C for 8 h to obtain a solid powder; S2: calcining the solid powder at 500° C. for 3 h in an air atmosphere to obtain a composite positive electrode material.

[0022] The Na 0.67 Ni 0.23 Mn 0.67 V 0.1 The preparation method of O2 precursor is as follows: A1: 60g sodium source, 15g nickel source, 70g manganese source, 15g vanadium pentoxide, and 0.08g grinding aid were mixed evenly; A2: Add the mixture into a ball mill at 300 r / min, add 50 g of anhydrous ethanol, ball mill for 90 min, and dry; A3: The ball-milled powder was pressed into a sheet, placed in a muffle furnace, calcined at 700°C for 8 hours in an air atmosphere, and then cooled to room temperature to obtain Na 0.67 Ni 0.23 Mn 0.67 V 0.1 O2 precursor.

[0023] The preparation method of Na3V2O2(PO4)2F is as follows: B1: Add 15g V2O5 and 30g oxalic acid to 60g deionized water and stir at 60℃ for 40min; B2: Add 10g NaF and 8g NH2H2PO4 to 10g deionized water, stir to dissolve, and then add to the solution of B1; B3: The solution obtained in B2 was placed in a polytetrafluoroethylene autoclave, and subjected to hydrothermal treatment at 150°C for 8 hours in a forced air drying oven, and then cooled to room temperature; the blue substance was washed with deionized water three times, and finally dried at 60°C for 8 hours; B4: Then, under N2 atmosphere, the powder obtained in B3 was sintered at 500°C at a rate of 3°C per minute for 90 min to obtain Na3V2O2(PO4)2F.

[0024] The sodium source is sodium carbonate.

[0025] The nickel source is nickel oxide.

[0026] The manganese source is manganese sulfate.

[0027] The preparation method of the grinding aid is: The stirred kettle was kept under nitrogen conditions for 10 minutes, and 10g of vanadium dimercaptosuccinate, 30g of sodium oleate, 2g of styryl boric acid diethanolamine ester (CAS No. 411222-52-1), 200g of toluene and 3g of sodium ethoxide were stirred and reacted at 80°C for 100 minutes. After the reaction was completed, the toluene was removed by vacuum distillation to obtain a grinding aid.

[0028] The preparation method of vanadium dimercaptosuccinate is as follows: 20 g of dimercaptosuccinic acid, 18 g of vanadium nitrate and 500 g of water are stirred and reacted at 40° C. for 100 min, and the water is distilled off to obtain vanadium dimercaptosuccinate.

[0029] Example 2 A method for preparing a composite positive electrode material, the operating steps of which are: S1: During the coating process, 85gNa 0.67 Ni 0.23 Mn 0.67 V 0.1 The O2 precursor was evenly distributed in 240 g of anhydrous alcohol solution; then 4 g of Na3V2O2(PO4)2F was added, and after 9 h of thorough mixing and strong stirring, it was dried at 55°C for 9 hours to obtain a solid powder; S2: The solid powder is calcined at 550° C. for 4 h in an air atmosphere to obtain a composite positive electrode material.

[0030] The Na 0.67 Ni 0.23 Mn0.67 V 0.1 The preparation method of O2 precursor is as follows: A1: 63g sodium source, 16g nickel source, 73g manganese source, 16g vanadium pentoxide, and 0.1g grinding aid were mixed evenly; A2: Add the mixture into a ball mill at 350 r / min, add 55 g of anhydrous ethanol, ball mill for 100 min, and dry; A3: The ball-milled powder was pressed into a sheet, placed in a muffle furnace, calcined at 800°C for 9 hours in an air atmosphere, and then cooled to room temperature to obtain Na 0.67 Ni 0.23 Mn 0.67 V 0.1 O2 precursor.

[0031] The preparation method of Na3V2O2(PO4)2F is as follows: B1: Add 16g V2O5 and 33g oxalic acid to 63g deionized water and stir at 65°C for 45min; B2: Add 12g NaF and 9g NH2H2PO4 to 13g deionized water, stir to dissolve, and then add to the solution of B1; B3: The solution obtained in B2 was placed in a polytetrafluoroethylene autoclave, and subjected to hydrothermal treatment at 155°C for 9 hours in a forced air drying oven, and then cooled to room temperature; the blue substance was washed with deionized water three times, and finally dried at 65°C for 9 hours; B4: Then, under N2 atmosphere, the powder obtained in B3 was sintered at 550°C at a rate of 3°C per minute for 100 min to obtain Na3V2O2(PO4)2F.

[0032] The sodium source is sodium hydroxide.

[0033] The nickel source is nickel oxide.

[0034] The manganese source is manganese oxide.

[0035] The preparation method of the grinding aid is: The stirred kettle was kept under nitrogen conditions for 15 minutes, and 13g of vanadium dimercaptosuccinate, 35g of sodium oleate, 3g of styryl boric acid diethanolamine ester CAS No. 411222-52-1, 240g of toluene, and 4g of sodium ethoxide were stirred and reacted at 85°C for 110 minutes. After the reaction was completed, the toluene was removed by vacuum distillation to obtain a grinding aid.

[0036] The preparation method of vanadium dimercaptosuccinate is as follows: 25 g of dimercaptosuccinic acid, 24 g of vanadium nitrate and 550 g of water were stirred and reacted at 45° C. for 110 min, and the water was distilled off to obtain vanadium dimercaptosuccinate.

[0037] Example 3 A method for preparing a composite positive electrode material, the operating steps of which are: S1: During the coating process, 95gNa 0.67 Ni 0.23 Mn 0.67 V 0.1 The O2 precursor was evenly distributed in 280 g of anhydrous alcohol solution; then 6 g of Na3V2O2(PO4)2F was added, and after 11 h of thorough mixing and strong stirring, it was dried at 55°C for 11 h to obtain a solid powder; S2: calcining the solid powder at 600° C. for 4 h in an air atmosphere to obtain a composite positive electrode material.

[0038] The Na 0.67 Ni 0.23 Mn 0.67 V 0.1 The preparation method of O2 precursor is as follows: A1: 68g sodium source, 18g nickel source, 78g manganese source, 18g vanadium pentoxide, and 0.3g grinding aid were mixed uniformly; A2: Add the mixture into a ball mill at 350 r / min, add 65 g of anhydrous ethanol, ball mill for 110 min, and dry; A3: The ball-milled powder was pressed into a sheet, placed in a muffle furnace, calcined at 900°C for 11 hours in an air atmosphere, and then cooled to room temperature to obtain Na 0.67 Ni 0.23 Mn 0.67 V 0.1 O2 precursor.

[0039] The preparation method of Na3V2O2(PO4)2F is as follows: B1: Add 18g V2O5 and 38g oxalic acid to 68g deionized water and stir at 65°C for 55min; B2: Add 14g NaF and 11g NH2H2PO4 to 18g deionized water, stir to dissolve, and then add to the solution of B1; B3: The solution obtained in B2 was placed in a polytetrafluoroethylene autoclave, and subjected to hydrothermal treatment at 165°C for 11 hours in a forced air drying oven, and then cooled to room temperature; the blue substance was washed with deionized water three times, and finally dried at 65°C for 11 hours; B4: Then, under N2 atmosphere, the powder obtained in B3 was sintered at 600°C at a rate of 3°C per minute for 110 min to obtain Na3V2O2(PO4)2F.

[0040] The sodium source is sodium bicarbonate.

[0041] The nickel source is nickel hydroxide.

[0042] The manganese source is manganese oxide.

[0043] The preparation method of the grinding aid is: The stirred kettle was kept under nitrogen conditions for 25 minutes, and 18g of vanadium dimercaptosuccinate, 45g of sodium oleate, 4g of styryl boric acid diethanolamine ester CAS No. 411222-52-1, 280g of toluene, and 6g of sodium ethoxide were stirred and reacted at 85°C for 140 minutes. After the reaction was completed, the toluene was removed by reduced pressure distillation to obtain a grinding aid.

[0044] The preparation method of vanadium dimercaptosuccinate is as follows: 35 g of dimercaptosuccinic acid, 32 g of vanadium nitrate and 650 g of water were stirred and reacted at 45° C. for 140 min, and the water was distilled off to obtain vanadium dimercaptosuccinate.

[0045] Example 4 A method for preparing a composite positive electrode material, the operating steps of which are: S1: During the coating process, 100gNa 0.67 Ni 0.23 Mn 0.67 V 0.1 The O2 precursor was evenly distributed in 300 g of anhydrous alcohol solution; then 7 g of Na3V2O2(PO4)2F was added, and after 12 h of thorough mixing and strong stirring, the mixture was dried at 60 °C for 12 h to obtain a solid powder; S2: The solid powder is calcined at 650° C. for 5 h in an air atmosphere to obtain a composite positive electrode material.

[0046] The Na 0.67 Ni 0.23 Mn 0.67 V 0.1 The preparation method of O2 precursor is as follows: A1: 70g sodium source, 20g nickel source, 80g manganese source, 20g vanadium pentoxide, and 0.4g grinding aid were mixed evenly; A2: Add the mixture into a ball mill at 400 r / min, add 70 g of anhydrous ethanol, ball mill for 120 min, and dry; A3: The ball-milled powder was pressed into a sheet, placed in a muffle furnace, calcined at 950°C for 12 hours in an air atmosphere, and then cooled to room temperature to obtain Na 0.67 Ni 0.23 Mn 0.67 V 0.1 O2 precursor.

[0047] The preparation method of Na3V2O2(PO4)2F is as follows: B1: Add 20g V2O5 and 40g oxalic acid to 70g deionized water and stir at 70℃ for 60min; B2: Add 15g NaF and 12g NH2H2PO4 to 20g deionized water, stir to dissolve, and then add to the solution of B1; B3: The solution obtained in B2 was placed in a polytetrafluoroethylene autoclave, and subjected to hydrothermal treatment at 170°C for 12 hours in a forced air drying oven, and then cooled to room temperature; the obtained blue substance was washed with deionized water three times, and finally dried at 70°C for 12 hours; B4: Then, under N2 atmosphere, the powder obtained in B3 was sintered at 650°C at a rate of 3°C per minute for 120 min to obtain Na3V2O2(PO4)2F.

[0048] The sodium source is sodium chloride.

[0049] The nickel source is nickel hydroxide.

[0050] The manganese source is manganese carbonate.

[0051] The preparation method of the grinding aid is: The stirred kettle was kept under nitrogen conditions for 30 minutes, and 20g of vanadium dimercaptosuccinate, 50g of sodium oleate, 5g of styryl boric acid diethanolamine ester (CAS No. 411222-52-1), 300g of toluene and 7g of sodium ethoxide were stirred and reacted at 90°C for 150min. After the reaction was completed, the toluene was removed by vacuum distillation to obtain a grinding aid.

[0052] The preparation method of vanadium dimercaptosuccinate is as follows: 40 g of dimercaptosuccinic acid, 36 g of vanadium nitrate and 700 g of water are stirred and reacted at 50° C. for 150 min, and the water is distilled off to obtain vanadium dimercaptosuccinate.

[0053] Comparative Example 1 No grinding aid was added, and the other procedures were the same as in Example 1.

[0054] Comparative Example 2 No sodium oleate was added, and the other steps were the same as in Example 1.

[0055] Comparative Example 3 The other steps were the same as in Example 1 except that styryl boric acid diethanolamine ester was not added.

[0056] First charge and discharge efficiency / % Capacity retention rate after 200 cycles / % Example 1 92.8 96.9 Example 2 93.4 97.3 Example 3 93.9 97.8 Example 4 94.6 98.2 Comparative Example 1 77.5 72.6 Comparative Example 2 86.9 83.5 Comparative Example 3 87.6 84.1 Through the data analysis of the above embodiments and comparative examples, the composite positive electrode material prepared by the present invention has excellent electrochemical properties and cycle stability.

[0057] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a composite positive electrode material, the operating steps of which are: S1: During the coating process, 80-100 parts of Na 0.67 Ni 0.33-x Mn 0.67 V x The O2 precursor is evenly distributed in 200-300 parts of anhydrous alcohol solution; then 3-7 parts of Na3V2O2(PO4)2F are added, and after 8-12 hours of thorough mixing and strong stirring, the mixture is dried at 50-60°C for 8-12 hours to obtain a solid powder; S2: calcining the solid powder at 500-650° C. for 3-5 h in an air atmosphere to obtain a composite positive electrode material.

2. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The Na 0.67 Ni 0.33-x Mn 0.67 V x The preparation method of O2 precursor is as follows: A1: 60-70 parts of sodium source, 15-20 parts of nickel source, 70-80 parts of manganese source, 15-20 parts of vanadium pentoxide, and 0.08-0.4 parts of grinding aid are mixed uniformly; A2: Add the mixture into a ball mill at 300-400 r / min, add 50-70 parts of anhydrous ethanol, ball mill for 90-120 minutes, and dry; A3: The ball-milled powder is pressed into a sheet, placed in a muffle furnace, calcined at 700-950°C for 8-12 hours in an air atmosphere, and then cooled to room temperature to obtain Na 0.67 Ni 0.33-x Mn 0.67 V x O2 precursor.

3. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The preparation method of Na3V2O2(PO4)2F is as follows: B1: Add 15-20 parts of V2O5 and 30-40 parts of oxalic acid to 60-70 parts of deionized water and stir at 60-70°C for 40-60 minutes; B2: Add 10-15 parts of NaF and 8-12 parts of NH2H2PO4 to 10-20 parts of deionized water, stir to dissolve, and then add to the solution of B1; B3: The solution obtained in B2 is placed in a polytetrafluoroethylene autoclave, and subjected to hydrothermal treatment at 150-170°C for 8-12 hours in a forced air drying oven, and then cooled to room temperature; the obtained blue substance is washed with deionized water three times, and finally dried at 60-70°C for 8-12 hours; B4: Then, under N2 atmosphere, the powder obtained in B3 was sintered at 500-650°C at a rate of 3°C per minute for 90-120 min to obtain Na3V2O2(PO4)2F.

4. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The sodium source is one of sodium carbonate, sodium hydroxide, sodium bicarbonate and sodium chloride.

5. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The nickel source is one of nickel oxide and nickel hydroxide.

6. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The manganese source is one of manganese sulfate, manganese oxide and manganese carbonate.

7. The method for preparing a composite positive electrode material according to claim 2, characterized in that: The preparation method of the grinding aid is: The stirred kettle is kept under nitrogen condition and nitrogen is flushed for 10-30 minutes. 10-20 parts of vanadium dimercaptosuccinate, 30-50 parts of sodium oleate, 2-5 parts of styryl boric acid diethanolamine ester (CAS No. 411222-52-1), 200-300 parts of toluene and 3-7 parts of sodium ethoxide are stirred and reacted at 80-90° C. for 100-150 minutes. After the reaction is completed, toluene is removed by reduced pressure distillation to obtain a grinding aid.

8. The method for preparing a composite positive electrode material according to claim 7, characterized in that: The preparation method of vanadium dimercaptosuccinate is as follows: According to weight, 20-40 parts of dimercaptosuccinic acid, 18-36 parts of vanadium nitrate and 500-700 parts of water are stirred for reaction at 40-50° C. for 100-150 minutes, and water is distilled off to obtain vanadium dimercaptosuccinate.

Citation Information

Patent Citations

  • A sodium battery cathode material, its preparation method, and its application

    CN115133002B

  • Method for preparing sodium battery positive electrode material with high-configuration entropy surface layer by solid phase method

    CN116435481A

  • A doped and coated sodium battery positive electrode material, preparation method and use thereof

    CN117069162B